Impact of Laser Texturing on Ni-Based Single Crystal Superalloys - Lucille Despres (MDPI AG, 2021)
Surface laser texturing is used to ensure mechanical anchoring and strengthen adhesion between the interfaces of bond coatless thermal barrier coating system. To anticipate a possible loss of mechanical properties and to adapt to the perpetual evolutions of chemical compositions of the system, we analyzed the microstructural evolutions of different Ni-based single crystal superalloys, induced during infrared nanosecond laser ablation. Localized asperities composed of a melted, re-solidified matter, with a different microstructure from that of the bulk material, were generated. Regarding asperity morphologies, recrystallization within the latter could be avoided. Then, to compare different Ni-base single crystal superalloys, the thermal-affected volumes were characterized for two patterns textured under different energetic conditions. It seems that all the studied single crystal superalloys behaved quite similarly during nanosecond laser ablation. Finally, according to these results, ablation kinetics between the γ and γ′ phases of Ni-based superalloys could not be homogeneous.